Peroxidation of n-3 Polyunsaturated Fatty Acids Inhibits the Induction of iNOS Gene Expression in Proinflammatory Cytokine-Stimulated Hepatocytes - Araki, Yoshiro (Hindawi Publishing Corporation, 2011)
Eicosapentaenoic acid and docosahexaenoic acid (EPA/DHA), n-3 polyunsaturated fatty acids (PUFAs), have a variety of biological activities including anti-inflammatory and anticancer effects. We hypothesized that their peroxidized products contributed in part to anti-inflammatory effects. In the liver, the production of nitric oxide (NO) by inducible nitric oxide synthase (iNOS) has been implicated as one of the factors in hepatic inflammation and injury. We examined whether the peroxidation of EPA/DHA influences the induction of iNOS and NO production in proinflammatory cytokine-stimulated cultured hepatocytes, which is in vitro liver inflammation model. Peroxidized EPA/DHA inhibited the induction of iNOS and NO production in parallel with the increased levels of their peroxidation, whereas unoxidized EPA/DHA had no effects at all. Peroxidized EPA/DHA reduced the activation of transcription factor, NF-κB, and the expression of the iNOS antisense transcript, which are involved in iNOS promoter transactivation (mRNA synthesis) and its mRNA stabilization, respectively. These findings demonstrated that peroxidized products of EPA/DHA suppressed the induction of iNOS gene expression through both of the transcriptional and posttranscriptional steps, leading to the prevention of hepatic inflammation.